PENGARUH MOTIVASI DAN KEPUASAN KERJA KARYAWAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DI CV SUPRATEX - Antonio, Nio Erick (Agora, 2014)
This study was conducted to determine the effect of employee motivation and job satisfaction on organizational citizenship behavior in CV Supratex. The population in this study amounted to 200 employees of CV Supratex. The samples used were 81 people from the processing and production division. The sampling method used is judgment sampling. This research was a quantitative research as well as data obtained from the completed questionnaire by 81 respondents. The analytical method used was linear regression multiplied. The results of this study indicate that work motivation variable had a positive and significant influence on organizational citizenship behavior variables. Variable job satisfaction also had a positive and significant influence on organizational citizenship behavior, and these two variables also had an influence on OCB simultaneously. Motivation and job satisfaction variables had the same influence on OCB and dominated by job satisfaction. Improved behavior of organizational citizenship behavior CV Supratex expected to help in improving the performance of employees who are not directly impact on increasing production and efficiency levels of the company.